2006
DOI: 10.1111/j.1365-2036.2006.03146.x
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review: managing anaemia in Crohn's disease

Abstract: SUMMARY BackgroundAnaemia is a serious complication of Crohn's disease that triggers hospitalization and, if not interfered with, may lead to death.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
270
1
29

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 291 publications
(307 citation statements)
references
References 138 publications
7
270
1
29
Order By: Relevance
“…The anemia common to patients with IBD is mainly due to iron deficiency from blood loss, either alone or in combination, and suppression of erythropoiesis and iron binding (17,18) due to proinflammatory cytokine activity. There has been support for aggressively treating anemia in IBD using iron therapy for those who are iron deficient and using erythropoietin for subjects with impaired red blood cell production (15,(18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The anemia common to patients with IBD is mainly due to iron deficiency from blood loss, either alone or in combination, and suppression of erythropoiesis and iron binding (17,18) due to proinflammatory cytokine activity. There has been support for aggressively treating anemia in IBD using iron therapy for those who are iron deficient and using erythropoietin for subjects with impaired red blood cell production (15,(18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%
“…Expert reviews have suggested the use primarily of serum ferritin (with or without transferrin saturation) (18)(19)(20), with some indicating that the addition of sTfR could enhance the ascertainment of iron deficiency in IBD, considering that serum ferritin is an acute phase reactant and thus can be difficult to interpret in the presence of inflammation (19,20). Soluble transferrin receptor (sTfR) is thought to be more sensitive than ferritin at detecting iron deficiency, although the incremental utility of this index continues to be debated (24,25).…”
Section: Introductionmentioning
confidence: 99%
“…As absorption is erratic and incomplete, in our practices, we avoid oral formulations after bariatric surgery where absorption is marginal, in inflammatory bowel disease where oral iron can worsen symptoms [24,25], and in patients with conditions associated with a rate of blood loss that exceeds the ability of the absorptive process to keep up with the losses, such as heavy uterine bleeding and hereditary hemorrhagic telangiectasia (Osler-Weber-Rendu).…”
mentioning
confidence: 99%
“…Inadequate monitoring and treatment leads to a worse quality of life [88,89] and increased morbidity and hospitalization [90][91][92] . Repeated loss of blood, and to a lesser extent malabsorption of iron are the main causes of iron deficiency in IBD [86] .…”
Section: Ibdmentioning
confidence: 99%